British domestic synchronous clocks 1930-1980 the rise and fall of a technology - Pook, L. P. (Springer International Publishing, 2015)
This book complements available one-make books on domestic synchronous clocks. It is also a history of science book that sets British domestic synchronous clocks, their manufacturers and technology in their social context. Part I covers the historical background, British domestic synchronous clock manufacturers and brands, how synchronous clocks work, domestic synchronous clock cases, practical advice on the servicing of domestic synchronous clocks, and analysis of the marketing and reliability of British domestic synchronous clocks. This analysis provides an explanation of the rise and eventual fall of their technology. Part II contains galleries of a selection of British domestic synchronous clocks, and of the movements with which they are fitted. There is a front and back view of each clock, together with a brief description. Views of each movement include views with the movement partly dismantled, together with a brief technical description of the movement. This profusely illustrated book is primarily for fellow enthusiasts, and is based on an extensive archive of information on domestic synchronous clocks, their movements, and their manufacturers. Current electrical regulations mean that professional clockmakers are reluctant to repair synchronous clocks. In fact, provided that they have not been mistreated, synchronous clocks are usually reliable, and quite easy to maintain.